STRATEGI PT. PLN (PERSERO) ULP LUBUK SIKAPING KABUPATEN PASAMAN DALAM MENGATASI TUNGGAKAN PELANGGAN - Muharami Azizah; Abdul Sadad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
PT. PLN (Persero) ULP Lubuk Attitude, Pasaman Regency is a company engaged in the distribution of electric power services, especially in the Pasaman Regency area. To support the running of the company's operational activities and to improve service to customers, it must be supported by a smooth flow of good company income. However, with the existence of arrears in electricity accounts from customers, especially household customers, which causes disruption of the company's financial condition. The purpose of this study was to determine the strategy of PT. PLN (Persero) ULP Lubuk Attitude, Pasaman Regency in overcoming customer arrears and knowing the inhibiting factors encountered by PT. PLN (Persero) ULP Lubuk Attitude Pasaman Regency in carrying out a strategy to overcome customer arrears. The theory used in this research is the strategy according to Hadari Nawawi. To answer these problems the researchers used a qualitative and descriptive approach. In this study the authors used data collection techniques in the form of interviews, observations, and documentation and then analyzed based on research problems. The results of this study indicate that the strategy of PT. PLN (Persero) ULP Lubuk Attitude, Pasaman Regency in dealing with customer arrears has generally been implemented, but has not been fully implemented effectively. The strategy of PT. PLN (Persero) ULP Lubuk Attitude, Pasaman Regency in overcoming customer arrears include: dissemination of invoices to customers, namely current customers, notification to all customers using loudspeakers installed on mobile cars, conducting socialization through social media, brochures and banners, recommending the customers to migrate to prepaid / tokens, renew their supporting media, bring in officers from house to house. There are obstacles in implementing the strategy of PT. PLN (Persero) ULP Lubuk Attitude, Pasaman Regency in overcoming customer arrears including conflicts with customers and the habits of customers who are late in paying. Keyword : Strategy, Arrears, Customers, Public Service